2004
DOI: 10.1002/elps.200305725
|View full text |Cite
|
Sign up to set email alerts
|

Native and sodium dodecyl sulfate‐capillary gel electrophoresis of proteins on a single microchip

Abstract: Simultaneous electrophoresis of both native and Sodium dodecyl sulfate (SDS) proteins was observed on a single microchip within 20 min. The capillary array prevented lateral diffusion of SDS components and avoided cross contamination of native protein samples. The planar sputtered electrode format provided a more uniform distribution of separation voltage into each of the 36 parallel microchannel capillaries than platinum wire electrodes commonly used in conventional electrophoresis. The customized geometry of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
(19 reference statements)
1
21
0
Order By: Relevance
“…Migration time of proteins at a distance of 2.5 cm vs. the molecular weight for four different polyacrylamide gels (6,8,10, and 12%). Tsai et al [8] reported Ferguson plots of four proteins with molecular weights between 32 and 85 kDa. The experiments were carried out in glass channels.…”
Section: Ferguson Plotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration time of proteins at a distance of 2.5 cm vs. the molecular weight for four different polyacrylamide gels (6,8,10, and 12%). Tsai et al [8] reported Ferguson plots of four proteins with molecular weights between 32 and 85 kDa. The experiments were carried out in glass channels.…”
Section: Ferguson Plotsmentioning
confidence: 99%
“…Yao et al [2] successfully separated six fluorescently labelled proteins ranging from 9 to 116 kDa in a glass microchannel, in less than 35 s. Tsai et al [8] also reported a simultaneous CGE of both native and SDS proteins in a glass device within 20 min.…”
Section: Introductionmentioning
confidence: 96%
“…For example, ion exchangebased separation may be substituted for ampholyte-based IEF in the first dimension, and size-based separation in the third dimension may be accomplished by capillary electrophoresis using polymers as a molecular sieve matrix that allows proteins to be resolved based on molecular mass (20 -22). Capillary electrophoresis in the third-dimension separation could be multiplexed to increase throughput and would facilitate protein recovery by eliminating the need for gel cutting and protein extraction from gels (23)(24)(25). Automation of the separation system can also be envisaged.…”
Section: Effect Of Immunodepletion Of Abundantmentioning
confidence: 99%
“…method provided the LODs of 0.1 ng/µL for fluorescently labeled proteins. A simultaneous electrophoretic separation of both native and denatured proteins (SDS-proteins) in 36 parallel microchannels on a single microchip within 20 min was demonstrated (Tsai et al, 2004). The versatile microchannel array with self-contained electrodes allows Ferguson plots of native and denatured proteins obtained and provides new opportunities for analysis of many different protein samples by a single separation run.…”
Section: Sievingmentioning
confidence: 99%